PSICOPOLÍTICA SURREALISTA: MARXISMO, PSICOANÁLISIS, VANGUARDISMO ARTÍSTICO Y CRÍTICA DE LA PSICOLOGÍA - Pavón Cuellar, David (Universidad de Costa Rica, 2018)
Modern psychology, as a scientific-professional specialty and as popularized and general knowledge spread in the social domain, rests on several assumptions, including the distinction of its object from everything else, including the body and the outer world. This article will show how this distinction and other psychological assumptions were implicitly or explicitly challenged in the 1920s and 1930s by certain conceptions of Marxist-Freudian inspiration found in the artistic avant-gardes of French surrealism, the Czech poetic-surrealist movement, Brazilian anthropophagy and Latin American surrealism.